Reviewing the material and metal security of low-carbon energy transitions. (May 2020) - Lee, J.; Bazilian, M.; Sovacool, B.; Hund, K.; Jowitt, S.M.; Nguyen, T.P.; Månberger, A.; Kah, M.; Greene, S.; Galeazzi, C.; Awuah-Offei, K.; Moats, M.; et al.
Abstract: The global transition to a low-carbon economy will involve changes in material markets and supply chains on a hitherto unknown scale and scope. With these changes come numerous challenges and opportunities related to supply chain security and sustainability. To help support decision-making as well as future research, this study employs a problem-oriented perspective while reviewing academic publications, technical reports, legal documents, and published industry data to highlight the increasingly interconnected nature of material needs and geopolitical change. The paper considers a broad set of issues including technologies, material supplies, investment strategies, communal concerns, innovations, modeling considerations, and policy trends to help contextualize policy decisions and regulatory responses. Policy options are outlined for each topical section, as well as areas for further research. Together, these recommendations serve to help guide the complex, interdisciplinary approach to materials required for a low-carbon transition.